2022
DOI: 10.3390/buildings12071022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ground Motion Duration on the Seismic Performance of a Two-Storey Balloon-Type CLT Building

Abstract: The effects of long duration ground motions on the seismic performance of a newly constructed two-storey balloon-type cross-laminated timber (CLT) building located in Vancouver, Canada, was studied. A three-dimensional numerical model of the building was developed in OpenSees. The connection and shear wall models were validated with test data. Twenty-four pairs of long and short duration records with approximately the same amplitude, frequency content, and rate of energy build-up were used for nonlinear dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this way, insights can be obtained into the relative impact of ground motion duration. Many researchers have utilized this approach to gauge duration effects using single degree of freedom (SDOF) modeling [4][5][6][7] on the seismic performance of different structural systems, including bridges [8], reinforced concrete structures [9][10][11], and light-frame wood constructions [12][13][14][15]. In terms of steel moment frames, the focus of the current study, Liapopoulou et al [7], Chandramohan et al [16], and Hwang et al [17] found that long-duration ground motions resulted in a relatively 20%, 29%, and 43% reduction in median collapse capacity (i.e., median spectral acceleration of collapse at the fundamental period of buildings), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, insights can be obtained into the relative impact of ground motion duration. Many researchers have utilized this approach to gauge duration effects using single degree of freedom (SDOF) modeling [4][5][6][7] on the seismic performance of different structural systems, including bridges [8], reinforced concrete structures [9][10][11], and light-frame wood constructions [12][13][14][15]. In terms of steel moment frames, the focus of the current study, Liapopoulou et al [7], Chandramohan et al [16], and Hwang et al [17] found that long-duration ground motions resulted in a relatively 20%, 29%, and 43% reduction in median collapse capacity (i.e., median spectral acceleration of collapse at the fundamental period of buildings), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the performance-based design process, the structural safety assessment targets should be quantified according to the damage index [1][2][3]. A reasonable damage index not only reflects the damage caused by the three elements of the earthquake (amplitude, frequency spectrum, and earthquake duration) [4][5][6][7], but also establishes a corresponding relationship with the construction member parameters to improve the mechanical properties of the structure [8]. The existing damage index can be classified into three aspects: (a) degradation-based damage index; (b) deformation-based damage index; and (c) energy-based damage index.…”
Section: Introductionmentioning
confidence: 99%
“…Ground motion duration is a key parameter that considerably influences the seismic response of various types of structures [13][14][15][16][17][18][19][20][21]. In addition, ground motion duration is a key parameter for simulating ground motion recordings (used for nonlinear time history analyses of structures in areas with few available recordings) for various tectonic regimes and source-site distances.…”
Section: Introductionmentioning
confidence: 99%